2022
DOI: 10.1001/jamanetworkopen.2022.11065
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Treatment of Colorectal Cancer and Short-term Outcomes During the First Wave of the COVID-19 Pandemic in Sweden

Abstract: Key Points Question Did the treatment of colorectal cancer in Stockholm, Sweden, change during the COVID-19 pandemic? Findings In this cohort study of 1140 patients with colorectal cancer from the Swedish Colorectal Cancer Registry, the proportion of patients with colon cancer treated with ostomy almost doubled, from 17% in March to August 2019 to 30% in March to August 2020; short-term complications and time to surgery remained unchanged. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 37 publications
2
29
1
Order By: Relevance
“…Although the initial concern regarding the enhanced viral transmission related to aerosolisation associated with minimally invasive surgery was rapidly allayed by different societal guidelines, however, there have been reports of up to 20% decrease in minimally invasive surgeries for rectal cancer from some Chinese centres [ 45 ]. However, some European and American centres reported no difference in minimally invasive colorectal surgeries during Covid-19 pandemic with strict adherence to the societal guidelines [ 46 , 47 ]. Increase in minimally invasive colorectal surgeries during the Covid-19 era in our study may be explained by strict adherence to the precautionary measures adopted in these centres and benefits related to enhanced postoperative recovery and decreased respiratory complications.…”
Section: Discussionmentioning
confidence: 99%
“…Although the initial concern regarding the enhanced viral transmission related to aerosolisation associated with minimally invasive surgery was rapidly allayed by different societal guidelines, however, there have been reports of up to 20% decrease in minimally invasive surgeries for rectal cancer from some Chinese centres [ 45 ]. However, some European and American centres reported no difference in minimally invasive colorectal surgeries during Covid-19 pandemic with strict adherence to the societal guidelines [ 46 , 47 ]. Increase in minimally invasive colorectal surgeries during the Covid-19 era in our study may be explained by strict adherence to the precautionary measures adopted in these centres and benefits related to enhanced postoperative recovery and decreased respiratory complications.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, The COVIDSurg Collaborative, which analyzed 2073 patients in 40 countries operated on during the first wave of the pandemic, found that only 1.3% had a defunctioning stoma and only 3.0% had an end stoma instead of an anastomosis. 7 This finding is interesting and may, as the authors mention, 1 indicate that our Swedish colleagues may have decided during that time to opt for the procedure with the lowest risk of complications to avoid potential complications that may overload their overwhelmed intensive care units. This finding is another example of how colorectal surgeons had to adapt their practices and surgical decision-making to cope with the new reality set by the pandemic.…”
mentioning
confidence: 88%
“…The authors compared 550 patients with colorectal cancer treated between March and August 2020 with a control group of 590 patients treated between March and August 2019. 1 The authors reported that more patients during the pandemic presented with advanced stage cancers, mostly a higher proportion of T4 tumors, compared with the control patients in 2019. This finding is…”
mentioning
confidence: 99%
See 2 more Smart Citations